EXPLORING THE THERAPEUTIC POTENTIAL OF LOW-DOSE COLCHICINE IN CORONARY ARTERY DISEASE: AN IN-DEPTH ANALYSIS OF INFLAMMATION, SAFETY, AND CLINICAL EFFECTIVENESS - SRINIVAS, VARSHITHA; SURESH, SWATHY (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Coronary Artery Disease (CAD) is a prevalent cardiovascular illness that is a primary cause of morbidity and mortality globally. It is distinguished by the constriction or blockage of the coronary arteries, which limits blood circulation to the heart. Inflammation is a driving force in the pathophysiology of CAD. Colchicine is an anti-inflammatory medication that has lately been studied for its potential application in the treatment of CAD. Its multimodal method of action has sparked interest due to its ability to treat inflammation and lower the concentration of critical inflammatory biomarkers. Clinical evidence validates the safe and effective use of Colchicine in CAD. Several recommendations advocate the use of colchicine in the secondary prevention of CAD. This article discusses the use of low-dose colchicine in CAD, its function in inflammation, as well as its safety and therapeutic effectiveness.